Riding the Tide: Indigenous Knowledge, History and Water in a Changing Australia. (1st August 2008) - Goodall, Heather
Abstract : Indigenous people's knowledge of their environments, often called Traditional Environmental Knowledge [TEK], is widely invoked today in many arenas of environmental analysis and natural resource management as a potential source of beneficial approaches to sustainability. Indigenous knowledge is most often discussed in this literature and practice as if it were a static archive of data, largely unchanging since the point of colonisation and/or modernisation in the area under study. This paper discusses the contested and relational nature of indigeneity and challenges the ahistorical conceptualisation of indigenous knowledge. It does so by drawing on the work of historians and anthropologists to argue that indigenous knowledge, about environmental and other matters, should be seen as a process rather than an archive. This approach offers a way to understand how indigenous knowledge of environments might continue to be meaningful and relevant in conditions of rapid environmental change. A case study of one such situation is the upper Darling River region in Australia, colonised by the British from the 1840s. Water courses, springs and water holes have been critically important both in the conservation of indigenous environmental knowledge and in shaping the way it has developed in interaction with the long and challenging conditions of colonisation. Tracing the historical changes in indigenous knowledge offers the possibility not only of identifying continuing viable alternatives to western agricultural or conservation strategies but also of identifying environmental change over the time of colonisation, particularly in relation to areas associated with the passage and use of water.